Association Between Knowledge, Attitudes, and Healthy Eating Behaviors With Metabolic Syndrome at Nusa Cendana - Yesenia Belliani Dju; Ika Febianti Buntoro; Rahel Rara Woda; Herman Pieter Louis Wungouw (Pusat Riset dan Inovasi Nasional, 2025)
Background :Metabolic Syndrome (SM) is a condition in which a person has high blood pressure, central obesity and dyslipidemia, with or without hyperglycemics that occur at the same time. Metabolic syndrome can have an impact on cognitive decline, eating patterns and can increase the risk of non-communicable diseases also cardiovascular diseases.Aim :Knowing the relationship between knowledge, attitudes and behaviors of healthy eating patterns to the incidence of metabolic syndrome in the academic community of Nusa Cendana University.Method :This study used a correlation analytical research design with a Cross Sectional design with the examination carried out based on NCEP ATP III criteria and filled out a questionnaire of knowledge, attitudes and behaviors about healthy eating patterns. Data analysis used non-parametric test Chi square test. There is a significant relationship between knowledge, attitudes and behaviors of healthy eating patterns towards the incidence of metabolic syndrome in the academic community of Nusa Cendana University.